Cancer’s got nerve: Schwann cells drive perineural invasion - Salma H. Azam; Chad V. Pecot (The Journal of Clinical Investigation, 2016)
The invasion of cancer cells around and into nerves is associated with increased cancer aggression and poor patient outcome. As this perineural invasion increases disease severity, a better understanding of how the process is regulated may help in the development of therapeutics to target neuronal involvement in cancer. In this issue of the JCI, Deborde and colleagues show that direct contact between Schwann cells and cancer cells promotes cancer cell dissociation, migration, and invasion. Moreover, their data specifically suggest NCAM1 as an important molecular mediator of this Schwann cell–directed regulation of cancer cells in perineural invasion. The results of this study provide new insight into the cellular and molecular mechanisms of perineural invasion.